2002
DOI: 10.1097/00000658-200203000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Control Patterns in Acute Phase and Regenerating Human Liver Determined In Vivo by 31-Phosphorus Magnetic Resonance Spectroscopy

Abstract: ObjectiveTo elucidate the metabolic changes occurring within hepatocytes during acute phase reaction and liver regeneration. Summary Background DataThe metabolic events occurring within the liver during the hepatic stress response are poorly understood. The authors used in vivo 31-phosphorus magnetic resonance spectroscopy to study hepatic metabolism after surgical trauma with and without loss of liver cell mass. MethodsThree groups were studied: five patients undergoing partial hepatectomy; five patients in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 34 publications
2
28
0
1
Order By: Relevance
“…24 To an extent, these tasks are competing, as cells that undergo mitosis do not contribute towards detoxification while functioning cells cannot enter the mitotic phase to aid in liver regeneration. 7,25 Both tasks, however, increase the metabolic requirements and necessitate adequate energy production; as the capacity to produce energy increases, liver function recovers. 7 Phosphorus is central to biologic energy transformation and a major ingredient of ATP which, in turn, induces the expression of genes that activate the hepatocyte cell cycle and therefore liver regeneration.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…24 To an extent, these tasks are competing, as cells that undergo mitosis do not contribute towards detoxification while functioning cells cannot enter the mitotic phase to aid in liver regeneration. 7,25 Both tasks, however, increase the metabolic requirements and necessitate adequate energy production; as the capacity to produce energy increases, liver function recovers. 7 Phosphorus is central to biologic energy transformation and a major ingredient of ATP which, in turn, induces the expression of genes that activate the hepatocyte cell cycle and therefore liver regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…7,25 Both tasks, however, increase the metabolic requirements and necessitate adequate energy production; as the capacity to produce energy increases, liver function recovers. 7 Phosphorus is central to biologic energy transformation and a major ingredient of ATP which, in turn, induces the expression of genes that activate the hepatocyte cell cycle and therefore liver regeneration. To date, nearly all previous studies have only indirectly assessed the role of phosphorus by using clinical surrogates of liver regeneration such as postoperative liver failure and delayed recovery of liver function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…48,49 Our group has previously demonstrated that in humans, intraoperative deterioration in mitochondrial oxidative phosphorylation can be caused by prolonged hepatic pedicle clamping and is associated with an increased risk of complications and worse posthepatectomy liver function. 47 More recently, we have explored mitochondrial function and biogenesis in twostage hepatectomies with portal vein ligation and confirmed these findings.…”
Section: Mitochondrial Bioenergetics and Posthepatectomy Liver Dysfmentioning
confidence: 99%